Exploring Viral Interactions in Clavibacter Species: In Silico Analysis of Prophage Prevalence and Antiviral Defenses - Lucía Margarita Rubí-Rangel; Josefina León-Félix; Claudia Villicaña (Life)
Clavibacter is a phytopathogenic genus that causes severe diseases in economically important crops, yet the role of prophages in its evolution, pathogenicity, and adaptation remains poorly understood. In this study, we used PHASTER, Prophage Hunter, and VirSorter2 to identify prophage-like sequences in publicly available Clavibacter genomes. Prophage predictions were checked by hand to make them more accurate. We identified 353 prophages, predominantly in chromosomes, with some detected phage-plasmids. Most prophages exhibited traits of advanced domestication, such as an unimodal genome length distribution, reduced numbers of integrases, and minimal transposable elements, suggesting long-term interactions with their bacterial hosts. Comparative genomic analyses uncovered high genetic diversity, with distinct prophage clusters showing species-specific and interspecies conservation patterns. Functional annotation revealed prophage-encoded genes were involved in sugar metabolism, heavy metal resistance, virulence factors, and antibiotic resistance, highlighting their contribution to host fitness and environmental adaptation. Defense system analyses revealed that, despite lacking CRISPR-Cas, Clavibacter genomes harbor diverse antiviral systems, including PD-Lambda-1, AbiE, and MMB_gp29_gp30, some encoded within prophages. These findings underscore the pervasive presence of prophages in Clavibacter and their role in shaping bacterial adaptability and evolution.